2019
DOI: 10.17977/jptpp.v4i1.11911
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Pembelajaran Menulis Puisi Reflektif untuk Siswa SMA Kelas X

Abstract: <div align="center"><table width="645" border="1" cellspacing="0" cellpadding="0"><tbody><tr><td valign="top" width="439"><p><strong>Abstract:</strong> Writing poetry learning in school tends to be mechanistic and less direct students in creative process that cause difficulty and decrease students’ motivation on writing poetry. Therefore, the researcher develops poetry writing learning strategy, that is learning strategy of writing reflective poetry which is pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
1
0
1
Order By: Relevance
“…Teachers who used various strategies tried to utilize those strategies for several reasons: (1) the previous strategy had not been able to overcome difficulties in learning to write poetry, (2) boredom does not occur in learning, and (3) learning is expected to be more optimal. According to Purbarani et al (2019), the application of learning strategies for writing poetry that has yet to be varied will make students feel bored and reluctant to take part in learning to write poetry. The data above also found that teaching poetry writing can be done outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Teachers who used various strategies tried to utilize those strategies for several reasons: (1) the previous strategy had not been able to overcome difficulties in learning to write poetry, (2) boredom does not occur in learning, and (3) learning is expected to be more optimal. According to Purbarani et al (2019), the application of learning strategies for writing poetry that has yet to be varied will make students feel bored and reluctant to take part in learning to write poetry. The data above also found that teaching poetry writing can be done outside the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…The keyword used in this model is the word "is/are". Purbarani et al (2019) also offer a strategy for learning to write poetry that can be done with a reflective strategy, which is to raise the experiences that students live in real life. Students' real experiences will be directly involved in the creative process of writing poetry, considering that the source of writing does not come from life experiences that are experienced, felt, and lived.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penyebab sulitnya keterampilan menulis puisi karena minimnya aktivitas murid yang menjurus pada praktik menulis puisi di kelas dengan bantuan materi dan media pembelajaran yang tepat. Purbarani et al, (2019) (3) penarikan kesimpulan merupakan hasil penelitian yang menjawab fokus permasalahan dalam penelitian berdasarkan hasil analisis data. Kesimpulan disajikan dalam bentuk deskripsi objek penelitian dengan berpedoman pada kajian penelitian (Miles et al, 2014).…”
Section: Pendahuluanunclassified
“…The application of strategies in learning to write poetry as above is often considered trivial and light, but because the sources of writing that are raised do not come from experiences experienced, felt, and internalized by students, on the contrary, it actually makes students unable to be creatively involved in the process of writing poetry. As a result, student motivation will decrease and various other difficulties arise for students in the process of learning to write poetry [4]. One of the causal factors for the emergence of these obstacles, namely the teacher has not implemented innovative strategies in learning to write poetry so that students tend to be less interested in the lesson being taught.…”
Section: Introductionmentioning
confidence: 99%